Pengaruh Promosi Online dan Brand Ambassador terhadap Minat Beli Produk Scarlett Whitening - Romadon, Ahmad Sahri; Ihtiara, Febina Asza; Azzahra, Revy (STIE PENA, 2023)
This study aims to test the effect of online promotion through Instagram and brand ambassadors on the buying interest of Scarlett Whitening products. This study used a non-probability sampling technique with a total sample of 96 respondents. Using quantitative methods with a quantitative approach through a simple linear regression test as a statistical test calculation. The results of this study can be identified that the free variables in this study (Instagram social media and brand ambassadors) had a significant positive effect on the buying interest of Scarlett Whitening products. Keywords: Promotion Online; Brand Ambassador; Purchase Intention